2003
DOI: 10.1063/1.1626264
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of intersubband transitions in InAs/AlSb quantum wells

Abstract: We have carried out a systematic temperature-dependent study of intersubband absorption in InAs/AlSb quantum wells from 5 to 10 nm well width. The resonance energy redshifts with increasing temperature from 10 to 300 K, and the amount of redshift increases with decreasing well width. We have modeled the transitions using eight-band k⋅p theory combined with semiconductor Bloch equations, including the main many-body effects. Temperature is incorporated via band filling and nonparabolicity, and good agreement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Although the 2.6 meV larger shift in S3 reflects the stronger non-parabolicity and mixing with lh/so states of the hh2 state, the similar peak shift values of the two samples suggests the importance of the temperature dependence of E xc as in the case of the intersubband transitions in n-GaAs QWs 21 and n-InAs QWs. 22 Similarly to these QWs, we found that 9 peak shift due to the temperature dependence of the band parameters is one order of magnitude too small and cannot account for the experiment in p-SiGe QWs.…”
mentioning
confidence: 91%
“…Although the 2.6 meV larger shift in S3 reflects the stronger non-parabolicity and mixing with lh/so states of the hh2 state, the similar peak shift values of the two samples suggests the importance of the temperature dependence of E xc as in the case of the intersubband transitions in n-GaAs QWs 21 and n-InAs QWs. 22 Similarly to these QWs, we found that 9 peak shift due to the temperature dependence of the band parameters is one order of magnitude too small and cannot account for the experiment in p-SiGe QWs.…”
mentioning
confidence: 91%
“…An intersubband device should operate at and above 300 K, often with the condition of a negligible change in transition energy. Temperature dependence of the transition energy, up to room temperature, has been reported for intersubband absorption in InAs/AlSb multiple quantum well (MQW) structures [7] and for interband photoluminescence in nitride-based AlN/GaN MQW structures.…”
mentioning
confidence: 99%
“…An intersubband device should operate at and above 300 K, often with the condition of a negligible change in transition energy. Temperature dependence of the transition energy, up to room temperature, has been reported for intersubband absorption in InAs/AlSb multiple quantum well (MQW) structures [7] and for interband photoluminescence in nitride-based AlN/GaN MQW structures. [8] The huge piezoelectric fields introduce an additional temperature-dependent effect in the nitride MQW structures, because the different thermal expansions of AlN and GaN induce a temperature dependent strain in the structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This arises from how both the band-edges of the barriers and QWs are changing at approximately the same rate in energy and produce a negligible change in terms of the QW depth for both the HH and LH bands. 19,20 It is also evident from the spectra that there is a longer wavelength absorption peak appearing with the decreasing temperature at $10.2 lm wavelength. Most likely, the Fermi level enters the HH1 subband at low temperature, activating the HH1-HH2 transition.…”
mentioning
confidence: 86%